Evaluating the Impact of a Cream Containing Horse Placental Extract on Eye Corner Wrinkles in Healthy Women: Single-Blind Comparative Study - Tsuyuko Watanabe; Kentarou Tahara; Eiichi Hirano (JMIR Publications, 2023)
BackgroundPlacental extract has been mostly used in skin care for cosmetic purposes. However, the use of various placental extracts has been limited due to the lack of established and effective application methods. ObjectiveIn this study, we investigated the antiwrinkle effect of a cream formulation-LNC wrinkle eye cream (LNC-EC)-containing horse placental extract as the main ingredient. MethodsA total of 24 healthy women, aged 37-54 years, with wrinkle grades 1-3, were treated with LNC-EC for 2 weeks. The cream was applied on one-half of the participants' faces, and the results were compared with the untreated half of the face. ResultsVisual inspection, using the wrinkle grade standard, showed that the area treated with LNC-EC had a significantly lower wrinkle grade than the untreated area when comparing before and after the application of LNC-EC. In addition, replica analysis showed a significant reduction in both the maximum wrinkle width and the number of wrinkles in the LNC-EC-treated area in comparison to the untreated area before and after the application. These results suggest that LNC-EC has an antiwrinkle effect on the corners of the eyes based on parameters like the maximum wrinkle width and the number of wrinkles. ConclusionsLNC-EC, with horse placental extract as its main ingredient, was shown to be effective in improving wrinkles at the eye corners, presumably due to a reduction in the maximum wrinkle width and the number of wrinkles. Interpretation of the results is limited because this study was conducted only in the intervention group. A randomized controlled trial with a placebo control group is necessary to verify the antiwrinkle effects of horse placental extract.